2016
DOI: 10.1016/j.cbi.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipases and their inhibitors in health and disease

Abstract: Lipids play diverse and important biological roles including maintaining cellular integrity, storing fat for energy, acting as signaling molecules, and forming microdomains to support membrane protein signaling. Altering the levels of specific lipid species through activating or inactivating their biosynthetic or degradative pathways has been shown to provide either therapeutic benefit or cause disease. This review focuses on the functional, therapeutic, and (patho)physiological roles of lipases within the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 154 publications
(191 reference statements)
0
26
0
1
Order By: Relevance
“…f ). Blockage of LIPG activity with the LIPG inhibitor GSK264220A significantly reduced intracellular TAG levels (Fig. g ) and LD accumulation (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…f ). Blockage of LIPG activity with the LIPG inhibitor GSK264220A significantly reduced intracellular TAG levels (Fig. g ) and LD accumulation (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The known thieno [1,3]oxazines-4-ones 29 and 30 previously described as alternate substrate inhibitors of bCEase were found to exhibit high species-specific differences in their inhibitory potency, decreasing the activityo ft he human CEase to a much lesser extent than that of the murinea nd bovines isoenzymes owing to higherd issociation constants K i and the formation of catalytically active enzyme-inhibitor complexes. In the search for potent ands elective inhibitors of CEase, we applied an ew assay using the fluorogenic substrate 4-MUB on the recombinantly expressed murinea nd human isoenzymes, leadingt ot he identification of w-phthalimidoalkyl aryl ureas 2, 21,a nd 22.S tructure-activity relationship studies revealed that the urea moiety with an attached 3,5-bis(trifluoromethyl)phenyl group and the aromatic charactero ft he terminal phthalimide residue on the alkyl chain are crucial for the inhibitory activity of these compounds.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3] In this context, we are particularly interested in the bile salt-activated cholesterol esterase (CEase;E C3.1.1.13), a nonspecific serine hydrolase with variouss ubstrates including cholesteryl esters;t ri-, di-, and monoacylglycerols;p hospholipids;v itaminA esters; [4] and lipid amides. [1][2][3] In this context, we are particularly interested in the bile salt-activated cholesterol esterase (CEase;E C3.1.1.13), a nonspecific serine hydrolase with variouss ubstrates including cholesteryl esters;t ri-, di-, and monoacylglycerols;p hospholipids;v itaminA esters; [4] and lipid amides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations